Dependence in instrumental activities of daily living and its implications for older adults’ oral health - Saintrain, Maria (2021)
We aimed to assess the association between dependence in instrumental activities of daily living (IADL) and oral health in older adults. We conducted a cross-sectional study of 280 people aged 60 years served at public primary health care centers in Northeastern Brazil. Sociodemographic, oral discomfort and general health data were collected. The Lawton and Brody scale were used to assess IADL. This research adheres to the STROBE checklist. Most participants were married (n = 139; 49.6%), women (n = 182; 65.0%) and retired (n = 212; 75.7%). A total of 37 (13.2%) older adults had some degree of dependence in IADL. Dependence in IADL was associated with: retirement (p<0.040), poor general health (p = 0.002), speech problems (p = 0.014), use of medications (p = 0.021), difficulty chewing and swallowing food (p = 0.011), voice changes (p = 0.044), edentulism (p = 0.011), use of toothbrush (p<0.001), use of toothpaste (p<0.001), and visit to the dentist in the previous year (p = 0.020). Functional disability was associated with older age, cardiovascular diseases, speech problems, chewing and swallowing difficulties, use of medication and brushing deficiency. The functional dependence in IADL can be considered an indicator of oral health status in older adults.